An exploration into the level and characteristics of pain experienced by South African women treated for cervical cancer - Ilipo Kaila; Johanna E. Maree (Elsevier, 2018)
Despite the high incidence of cervical cancer in Africa, little is known about pain management in women treated for this disease as best practices primarily focus on the prevention of cervical cancer. The study aimed at describing pain in women diagnosed with cervical cancer who received radiotherapy with/without concurrent chemotherapy, before treatment and at six and 12 months after the completion of the treatment. A cross sectional design and calculated sample size were used to recruit 168 women (n = 168), 58 (n = 56) in each treatment group. Structured interviews were used to collect the data and the Brief Pain Inventory (BPI) served as the data collecting instrument. Descriptive statistics were used to analyse the data and the Kruskal-Wallis H Test determined statistical significant differences between the groups (p = 0.05). The majority of the respondents (78.0% n = 131) experienced disease related pain and most (73.9%; n = 85) experienced pain at the time of data collection. However, pain, on average, decreased after treatment and was at its lowest level six months after treatment but increased during the following six months. Pain influenced all the domains of function before treatment but improved after six months. There was a misfit between the level of pain and the type of analgesia used. In addition, most participants (58.3%; n = 67) took their pain medication only when needed. Our study highlighted the complexity of pain control, suggesting failure of both the healthcare professionals and the patients in achieving the ultimate goal of being pain free. Keywords: Cervical cancer, Pain, Radiotherapy